THE EFFECT OF SELF EFFICACY AND LEARNING INDEPENDENCE ON SELF REGULATED LEARNING IN STUDENTS OF SMK NEGERI 1 PERCUT SEI TUAN - Rahimah Azzahra Pohan; Hasanuddin; Salamiah Sari Dewi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to see the influence between Self Efficacy and Learning Independence with Self Regulated Learning in students of SMK Negeri 1 Percut Sei Tuan. The subjects of this study were students of SMK Negeri 1 Percut Sei Tuan with a sample of 96 students. With sampling through simple Proportionate Stratified Random Sampling.Data collection using a Likert scale consisting of three scales, namely the Self Efficacy scale, the Learning Independence scale and the Self Regulated Learning scale. The data analysis method used is Multiple Regression Analysis. The results of the study showed that in the first hypothesis there is a positive influence between Self Efficacy and Self Regulated Learning of students with a correlation coefficient of = 0.322 with a significance of p = 0.001 which means p <0.05. This means that the better the Self Efficacy, the better the Self Regulated Learning of students. The second hypothesis is known that there is an influence of Learning Independence on Self-regulated Learning of students. This is indicated by the correlation coefficient = = 0.691 and a significance of p = 0.001 which means p <0.05. This means that the better the Learning Independence, the better the Self Regulated Learning of students. And the third hypothesis shows that there is an influence of Self Efficacy and Learning Independence on Self-regulated Learning of students. This is indicated by F = 72.762 with p = 0.001 which means p <0.05. The correlation coefficient = 0.691 and the significance value of p = 0.001 which means p <0.05 and the coefficient of determination () of 0.61 which means Self Efficacy and Learning Independence have an influence on Self Regulated Learning with a contribution of 61%. Based on the results of the study, the hypothesis is accepted.